2018
DOI: 10.1016/j.jaci.2017.12.880
|View full text |Cite
|
Sign up to set email alerts
|

Blood Eosinophil Beta1-Integrin Activation Correlates with Eosinophilic Esophagitis (EoE) Disease Activity

Abstract: RATIONALE: Hypereosinophilia is defined as a peripheral blood absolute eosinophil count (AEC) of >0.5 x10 9 /L, while severe hypereosinophilia is defined as an AEC of >1.5x10 9 /L. Much has been published on hypereosinphilia in the adult literature; however, there is limited literature on pediatric patients with hypereosinophilia (especially severe eosinophila) or hypereosinophilic syndrome (HES). The goal of this study was to characterize children with severe hypereosinophilia hospitalized in a tertiary care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These "activated" eosinophils within circulation are more prone to arrest on endothelial-expressed VCAM-1 [39], and correlate with decreased lung function in subjects with mild asthma [40]. A similar scenario of activation of eosinophil-expressed β1 integrins appears to occur in EoE patients [41] and may correlate with disease activity [42]. Moreover, reports of two case studies demonstrated a higher percentage of CD274 + (PDL1) blood eosinophils in EoE with reduction back down to normal levels following successful treatment [43].…”
Section: Blood Eosinophilsmentioning
confidence: 93%
“…These "activated" eosinophils within circulation are more prone to arrest on endothelial-expressed VCAM-1 [39], and correlate with decreased lung function in subjects with mild asthma [40]. A similar scenario of activation of eosinophil-expressed β1 integrins appears to occur in EoE patients [41] and may correlate with disease activity [42]. Moreover, reports of two case studies demonstrated a higher percentage of CD274 + (PDL1) blood eosinophils in EoE with reduction back down to normal levels following successful treatment [43].…”
Section: Blood Eosinophilsmentioning
confidence: 93%